E-governance service deployment: an empirical study with structural equation model. (2017) - Patra, Prasant Kumar; Ray, Arun Kumar; Padhy, Ramakrushna K.
The deployment of e-governance in public organisations promises to connect better with citizens, boost public participation in government decision making, improve the efficiency of service delivery and information dissemination. While each of these outcomes is important for both, the government and its citizens; we know little about how various factors mediate the effectiveness of ICTs on producing these outcomes. This study tries to find out the factors responsible for the successful implementation of e-governance. Four factors related to technology, organisational, legal and regulatory aspects and implementation aspects are measured using latent variables and the causal relationship between them are captured in the hypothetical model. The hypotheses conceptualised in the study are tested using structural equation model and the relationships are established. The study results in some interesting findings. The results show that the technological aspects and the organisational aspects are dominant in influencing the implementation of electronic governance in the state of Odisha. The research findings show that the legal and regulatory policies are dictated by the change in technology. However, it has not much effect on the implementation of the electronic governance.